2016
DOI: 10.1261/rna.056226.116
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophore ligand binding and complex stabilization of the RNA Mango and RNA Spinach aptamers

Abstract: The effective tracking and purification of biological RNAs and RNA protein complexes is currently challenging. One promising strategy to simultaneously address both of these problems is to develop high-affinity RNA aptamers against taggable small molecule fluorophores. RNA Mango is a 39-nucleotide, parallel-stranded G-quadruplex RNA aptamer motif that binds with nanomolar affinity to a set of thiazole orange (TO1) derivatives while simultaneously inducing a 10-fold increase in fluorescence. We find that RNA Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 44 publications
5
60
0
Order By: Relevance
“…Contrarily, YO3-biotin fluoresces with comparable intensities when bound in either the Mango or the Spinach construct (Supplementary Fig. 2d, e ), similarly to what has been observed previously for TO1-biotin 30 . We further examined the binding affinities (EC 50 ) of the fluorophores in the two aptamers (Supplementary Table 1 ), and found that DFHBI-1T has a significantly lower EC 50 in Spinach than YO3-biotin (~340 nM compared to ~4 µM).…”
Section: Resultssupporting
confidence: 87%
“…Contrarily, YO3-biotin fluoresces with comparable intensities when bound in either the Mango or the Spinach construct (Supplementary Fig. 2d, e ), similarly to what has been observed previously for TO1-biotin 30 . We further examined the binding affinities (EC 50 ) of the fluorophores in the two aptamers (Supplementary Table 1 ), and found that DFHBI-1T has a significantly lower EC 50 in Spinach than YO3-biotin (~340 nM compared to ~4 µM).…”
Section: Resultssupporting
confidence: 87%
“…3d) and Mango-tagged 5S-RNA and U6-RNA foci (~2-3-fold fluorescence turn-on in fixed mammalian cells 25 ). The in vitroevolved dye-binding aptamers all feature G-quadruplex RNA folds 38,39 , and it has been shown that the dyes can bind other G-quadruplex RNAs non-specifically in cells 39 , possible contributing to diminished cellular contrast. It is important to note that other factors besides in vitro enhancement contribute to cellular contrast, including robust folding of the RNA tag in the cellular environment, temperature-and salt-dependent stability of the RNA-probe complex, and probe photobleaching properties.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro evolved dye-binding aptamers contain a G-quadruplex fold 37,38 which has been shown to complicate RNA folding in mammalian cells 39 . Furthermore, ligands for evolved aptamers with the G-quadruplex fold may bind other RNAs with G-quadruplex folds 39 , have been shown to bind nucleic acids nonspecifically 25 and G-quadruplex structures may be disrupted by dedicated helicases 40 . Thus, to improve folding and stabilize against RNase degradation in cells, such aptamers often include a folding scaffold when fused to mammalian RNAs [25][26][27]41 .…”
Section: Visualization Of Mrna Dynamics In Live Mammalian Cellsmentioning
confidence: 99%
“…Hence, very few literatures have shown the successful imaging in mammalian cells. In the comparison of fluorophore ligand binding and complex stabilization studies, the Mango has a large thermal stability and better discrimination from a broad range of small molecules [35] and the Corn shows improved photostability. Therefore, there are no doubt that the Mango and the Corn could be good tools to elucidate the working mechanism of cancers biology fields.…”
Section: New Mangomentioning
confidence: 99%
“…S. Yoon, J.J. Rossi / Advanced Drug Delivery Reviews 134 (2018)[22][23][24][25][26][27][28][29][30][31][32][33][34][35] …”
mentioning
confidence: 99%